How Did al-Suyuti Abridge Ibn Taymiyyaâs Nasihat Ahl al-Iman fi al-Radd âala Mantiq al-Yunan? - Ali, Mufti (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2008)
Al-Radd âala âl-Mantiqiyyin (an alternative title for Nasihat Ahl al-Iman) is a work composed by Ibn Taymiyya to demolish each principle of logic as well as to unravel the depravity of their foundation. Probably due to Ibn Taymiyyaâs being genius, when he destroys those principles, he could not avoid himself to discuss digressively irrelevant topics dealing with theological as well as metaphysical issues. In a number of passages in al-Radd, he could not even hinder himself to make a good deal of repetitions. Therefore, al-Radd âalaâl-Mantiqiyyin is complex and difficult to use. The coherence of arguments that Ibn Taymiyya formulated is not solid and comprehensive. His criticism of logic is not penetrating as well. On the basis of my analysis of al-Suyutiâs method of abridgement of Ibn Taymiyyaâs al-Radd, I argue that al-Suyuti succeeded in rendering Ibn Taymiyyaâs sequence of ideas superior to that found in the original work of the latter. The result of this study confirms Hallaqâs argument that the overall result of al-Suyutiâs abridgement of Ibn Taymiyyaâs al-Radd is âa more effective critique of logic than that originally formulated by Ibn Taymiyya